Digitalisasi Pemasaran Produk Lokal Kerajinan Limbah Sampah melalui Konsep Pemasaran Syariah bagi Pelaku UMKM - Iqbal, Muhammad; Putra, Megi Dwi; Dina, Yola Rahmah; Hasanah, Uswatun (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to enhance the capabilities of Micro, Small, and Medium Enterprises (MSMEs) in marketing waste craft products through a digital approach based on Sharia marketing principles. MSME actors in Jalan Pancur Mas, Sukarami Subdistrict, Selebar District, Bengkulu City, have significant potential in developing environmentally friendly local products. However, they still face challenges in conducting effective marketing that aligns with Islamic ethical principles. The program was carried out through training, mentoring in social media account creation, and the integration of Sharia values such as honesty, transparency, and fairness in promotional content development. The results of the activity show an increase in participants’ understanding of the importance of digital marketing and their ability to independently manage online marketing platforms ethically. This program is expected to be an initial step in building competitive MSMEs based on Islamic values.